Prior task experience affects temporal prediction and estimation - Tobin, Simon; Grondin, Simon (Frontiers in Psychology, 2015)
It has been shown that prior experience with a task improves temporal prediction, even when the amount of prior experience with the task is often limited. The present study targeted the role of extensive training on temporal prediction. Expert and intermediate runners had to predict the time of a 5km running competition. Furthermore, after the race’s completion, participants had to estimate their running time so that it could be compared with the initial predicted time. Results show that expert runners were more accurate than intermediate runners for both predicting and estimating their running time. Furthermore, only expert runners had an estimation that was more accurate than their initial prediction. The results confirm the role of prior task experience in both temporal prediction and estimation.